Estrategias lúdicas en el ámbito de expresión oral en preparatoria en la Escuela de Educación Básica “Capullitos” cantón Riobamba - Chimborazo Achi, Gisela Sthefania (2024)
This research is titled "Play Strategies in the Field of Oral Expression in High School at the CAPULLITOS Basic Education School, Riobamba City." The main objective of this research is to determine the playful strategies that contribute to strengthening oral expression in children. In this sense, this work represents a significant contribution to the educational field since there are factors that impede language development. Methodologically, this research has a qualitative approach, with a non-experimental design, and is complemented with a field study, considering the context and data collection, it also has bibliographic research maintaining a variety of relevant sources, as well as a transversal research since it covers a certain time for analysis. Within this context, the analysis and interpretation of the data collected will provide an understanding of the children's verbal language development level through observing a group of 22 students, facilitating the evaluation of linguistic development.